A taxonomically significant polymorphism in Leucochrysa (Neuroptera: Chrysopidae): Nomenclature, larval and adult descriptions, and biological notes - Tauber, Catherine A.; Mantoanelli, Euzileni; Albuquerque, Gilberto S.; Reguilón, Carmen; Olazo, Enrique González; Tauber, Maurice J. (Zootaxa, 2011)
Leucochrysa (Leucochrysa) loretana Navás, 1935, a species described from Argentina, was discovered to have a geographically variable polymorphism, with two forms of adult coloration. One of the morphs (the “brown-spotted” morph) is indistiguishable from the widespread species Leucochrysa (Leucochrysa) longicornis (G. Gray in Cuvier, 1832) and the second morph (the “white-spotted” morph) is identical to another Argentinian species, Leucochrysa (Leucochrysa) boxi Navás, 1930. These observations generated a number of nomenclatural changes: (1) The oldest of the three names, L. (L.) longicornis (= Hemerobius longicornis), is a secondary homonym of a Linnaean species described in 1764 and therefore is unavailable for Gray’s species. (2) Thus, by priority, L. (L.) boxi becomes the valid name for the polymorphic species. (3) Leucochrysa (L.) loretana becomes a synonym of L. (L.) boxi. (4) The above three names are stabilized by the designation of primary types for each of the species, and by other nomenclatural actions. Specifically, (a) a lectotype is designated for Hemerobius longicornis G. Gray and, as First Revisers, we selected the species name from among two that were published in the original description; (b) a lectotype is designated for Leucochrysa boxi Navás; and (c) a neotype is designated for Leucochrysa loretana Navás. Finally, the L. (L.) boxi adult is redescribed (both morphs, as well as the male and female genitalia); the larvae (all instars) are described; and aspects of the biology of the species (geographic variation in the polymorphism and a new record of ectoparasitism) are presented.